2008
DOI: 10.1111/j.1745-7254.2008.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of honokiol is mediated by PI3K/Akt pathway suppression

Abstract: Aim: In this study, we investigated the regulatory effects of honokiol on various inflammatory events mediated by monocytes/macrophages (U937/RAW264.7 cells) and lymphocytes (splenic lymphocytes and CTLL-2 cells) and their putative action mechanism. Methods: In order to investigate the regulatory effects, various cell lines and primary cells (U937, RAW264.7, CTLL-2 cells, and splenic lymphocytes) were employed and various inflammatory events, such as the production of inflammatory mediators, cell adhesion, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 51 publications
5
62
0
2
Order By: Relevance
“…3B, right panel) that was similar to its inhibitory effect on TNF-α production. It has been reported that honokiol blocks iNOS expression at the transcriptional level (9,13). Interestingly, honokiol inhibition appears to be lower in the toll like receptor 2 (TLR2)-mediated signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3B, right panel) that was similar to its inhibitory effect on TNF-α production. It has been reported that honokiol blocks iNOS expression at the transcriptional level (9,13). Interestingly, honokiol inhibition appears to be lower in the toll like receptor 2 (TLR2)-mediated signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that honokiol is capable of blocking a common pathway involved in the production of proinflammatory cytokines. Indeed, it has been reported that honokiol suppresses TNF-α production by suppressing a series of activation pathways composed of Akt, IKK, IκBα, and NF-κB, which is a signaling event generally seen under inflammatory conditions (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An impressive series of studies has shown that all of these major indicators are positively impacted by Magnolia lignans, even if the full anti-inflammatory mechanisms have not yet been elucidated (Choi et al, 2007;Lin et al, 2007;Munroe et al, 2007;Kang et al, 2008;Lee et al, 2011). Upregulating signaling cascades composed of Ras, Raf, and MAPK, downregulating the activation of NF-κB, and blocking NF-κB activation mediated by CD40 and latent membrane protein 1 are speculated to be the action mechanism of Magnolia lignans (Lin et al, 2007;Kim and Cho, 2008;Lee et al, 2011).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4)), non-receptor type tyrosine kinases (eg. Src and Syk), serine/threonine kinases (protein kinase C (PKC), PKA, PI3K, and AKT), MAPK, and various redox-sensitive transcription factors, such as NF-κB, are regarded as critical components participating in the process (Kim and Cho, 2008;Simmonds and Foxwell, 2008).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%